Individual performance optimization of elite cyclists - Oggiano, L.; Sætran, L.; Morten Bardal, L. (Proceedings of the 2nd International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2014)
The present work focuses on individual posture optimization with the aim to individually reduce the drag and increase the power output on six elite cylists. In order to be able to quantify the changes in drag, power output and VO2max, wind tunnel tests combined with power output and oxygen intake measurements were carried out on each of the athletes tested. Drag measurements were performed in the large scale wind tunnel at NTNU at a constant wind speed of 14.2m/s using a AMTI high frequency force plate. Simultaneously with the drag measurements, the volume of oxygen intake and the power output generated by the athletes during the test in different positions were acquired respectively with a Metamax II portable analyzer from Cortex Biophysic and a Tacx Bushido cycling rig. The main results show that lowering the handlebar while raising the seat in order to obtain a smaller frontal area and a straighter back, lowers the aerodynamic drag but will possibly affect the volume of oxygen int ake. The handlebar repositioning leaded to similar results and it might then be questionable whether it is worth reducing the air resistance if the athlete does not sit as comfortably. In most cases a lower handlebar positioning and a narrower set up of the handlebar resulted in a considerable drag reduction without compromising the volume of oxygen intake. Being the present work a preliminary test, no statistical results are presented but as an overall conclusion, it can be pointed out the need to couple drag force measurements with oxygen intake and power production measurements in order to have a clearer picture of the effectiveness of the wind tunnel testing.